The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12788/jhm.3145
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Hypoglycemia Following Treatment of Hyperkalemia in Hospitalized Patients

Abstract: H yperkalemia is common in hospitalized patients, with an estimated prevalence of 1%-10%. 1,2 Hyperkalemia can lead to life-threatening cardiac arrhythmias. The risk of arrhythmias increases with serum potassium values >6.5 mmol/L, and hyperkalemia is associated with increased in-hospital mortality. 3 Treatment for hyperkalemia is indicated by a combination of the absolute serum potassium level, the rate of change of potassium level, and the presence of electrocardiogram abnormalities.Intravenous insulin stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…Without standardized blood glucose measurement protocols, retrospective studies have reported posttreatment hypoglycemia rates of 8.7%-17.5% among all patients with hyperkalemia, 5,6 and 13% among patients with end-stage renal disease. 4 These estimates likely underestimate the true hypoglycemia rates as they measure blood glucose sporadically and are often outside the three-hour window of highest risk after insulin administration.…”
mentioning
confidence: 99%
“…Without standardized blood glucose measurement protocols, retrospective studies have reported posttreatment hypoglycemia rates of 8.7%-17.5% among all patients with hyperkalemia, 5,6 and 13% among patients with end-stage renal disease. 4 These estimates likely underestimate the true hypoglycemia rates as they measure blood glucose sporadically and are often outside the three-hour window of highest risk after insulin administration.…”
mentioning
confidence: 99%
“…Not all previous studies have analyzed body weight but there is evidence supporting this association. Boughton et al reported that patients who experienced hypoglycemia were on average 15 kg lighter than patients who did not have hypoglycemia 3 . Schafer et al noted an ordinal relationship between a lower body weight and the severity of hypoglycemia 4 .…”
Section: Discussionmentioning
confidence: 99%
“…IDT can be complicated by hypoglycemia, which is associated with increased morbidity and mortality. The estimated incidence of hypoglycemia ranges from 6 to 21% [3][4][5][6] . The variability in estimates is likely due to differences in the population studied, clinical setting, protocol for IDT, and the definition of hypoglycemia used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
B oughton et al 1 reported a high incidence of hypoglycemia resulting from glucose-with-insulin (GwI) infusion used to treat acute hyperkalemia. This has been reported by other investigators-particularly in subjects without preexisting diabetes 2 and resonates with the experiences of clinicians practicing in Internal Medicine or Diabetes.The authors suggested that patients at risk of hypoglycemia be identified and offered a regimen containing less insulin.
…”
mentioning
confidence: 99%